Cumulative Grade Point Average and Comprehensive Examination Results as Predictors of Certified Public Accountant Board Examinees’ Performance - Salcedo, Arnold; Salcedo, Shane S.; Marasigan, Renz P.; Guevarra, Rolly M.; Datu, Ednel T.; Aquino, Rachelle B. (Future Science / FSH-PH Publications, 2021)
The Certified Public Accountant Licensure Examinations among BS Accountancy graduates can be considered as the culminating direct measure on how an accountancy retention policy program in a school prepares students to becoming CPAs. This study is aimed to gauge how cumulative qualifying grade point average of a student from first year to fifth year college and the fifth year comprehensive exams serve as predictors for the CPA Board Exams for a university in Central Luzon, Philippines. To measure the quality of the predictors, October examinees from the graduating batch were the focus of the study. With five hundred fifty three (553) BS Accountancy coming from five alumni batches, three hundred fifty eight (358) passed, fifty five (55) are conditioned and one hundred twenty (120) have failed during the first take of comprehensive exams. Auditing theory, business law and taxation are the most difficult subjects with less than two thirds (< 2/3) of the first takers as passing the said subjects. Those with a CGPA of 1.554 or higher in the undergrad, finishing with latin honors have the highest probability of passing the board. A range of four percent (either -4% to +4%) serves as the average variance between fifth year comprehensive exams and board examination performance for all first takers. Both the CGPA (r=0.632) and comprehensive examinations (r=0.745) are moderate predictors of the board examinations which imply that the accountancy program for the university can still be improved to further prepare the students to become CPAs.